Mapping the media-language-environment nexus in Indonesian language education: A systematic review of scopus-indexed empirical evidence, 2022–2026 - Putri Wulandari; Ade Hikmat; Siti Zulaiha; Adhy Setia Putera (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
Digital media have expanded the pedagogical possibilities of language education, yet the empirical intersection between digital media, Indonesian language education, and students' environmental awareness remains weakly consolidated. This systematic review maps Scopus-indexed empirical evidence published between 2022 and 2026 to clarify how this media-language-environment nexus has been investigated. Guided by the SPIDER framework and reported in accordance with PRISMA 2020 principles, the review searched Scopus using Boolean combinations covering digital media, language or literacy learning, environmental awareness, educational participants or settings, and empirical design. The search identified 289 records; 115 articles were assessed at full-text stage, four studies met the criteria for thematic synthesis, and nine were retained as peripheral contextual evidence. A descriptive quality appraisal was conducted using domains adapted from the Mixed Methods Appraisal Tool. The synthesis identified four patterns of digital media integration: social media content for sustainability thinking, digital comics for ecoliteracy, digital teaching materials for environmental education in Indonesian language learning, and audiovisual narratives for eco-centric language tasks. The small included corpus does not support generalizable causal claims. Instead, it reveals a fragmented but theoretically meaningful research space that requires clearer construct operationalization, validated environmental-awareness instruments, and stronger classroom-based designs in Indonesian language education.